Consumer perception and behaviour towards halal store-brand products and repurchase intention: insights for marketing strategy - Isa, Maryam Ladi; Kamarulzaman, Nitty Hirawaty; Hashim, Haslinda; Abdul Halim Lim, Sarina (Human Resource Management Academic Research Society, 2024)
In recent years, the halal market has experienced significant growth globally, driven by increasing consumer awareness and demand for halal-certified products. This study aimed to examine the determinants of consumer behaviour and brand relationships in the Malaysian halal market, providing insights to inform targeted marketing strategies for halal store-brand products. Our findings revealed that, halal store-brand awareness shows a strong positive effect (coefficient: 0.294, p < 0.001). Halal store-brand loyalty (coefficients: 0.199, p <0.001), attitude (coefficients: 0.262, p < 0.001) and Perceived behavioural control (coefficient: 0.223, p < 0.001) also positively impact repurchase intention. However, halal store-brand association exhibits a negative impact on repurchase intention (coefficient: -0.129, p < 0.05). Halal storebrand perceived quality weakly influences repurchase intention (coefficient: 0.110, p < 0.1). Subjective norms do not significantly influence repurchase intention (p > 0.1). Halal storebrand association mediates the effect of halal store-brand image, perceived value, trust, price and satisfaction. Findings revealed that, halal store-brand image (coefficient is positive 0.454, p < 0.000), halal store-brand perceived value (coefficient: 0.184, p < 0.001), halal store-brand satisfaction (coefficient: 0.180, p < 0.003) positively affect halal store-brand association. Halal store-brand trust, and price, do not significantly influence halal store-brand association. Overall, factors like halal store-brand awareness, halal store-brand loyalty, halal store-brand image, halal store-brand perceived value, attitude, and perceived behavioural control play significant roles in shaping consumers repurchase intention for halal store-brand products. This study recommends that companies focusing on halal store-brand products prioritize strategies to enhance brand awareness, loyalty, image, satisfaction, perceived value, attitude and perceived behavioural control among consumers. Investing in marketing campaigns to increase awareness, fostering strong relationships with consumers to build loyalty and maintaining consistent product quality can bolster repurchase intention. Additionally, efforts should be made to reinforce positive image and attitudes towards the brand through effective communication and engagement strategies. Furthermore, improving perceived value through product differentiation and highlighting unique benefits can strengthen brand association.